International Society for the History of Pharmacy : ISHP - Internationale Gesellschaft für Geschichte der Pharmazie (2016)
[Dt.:] Die Internationale Gesellschaft für Geschichte der Pharmazie bildet ein internationales, gemeinnütziges Zentrum für alle pharmazeutischen Themen mit historischem Zusammenhang. Sie fördert die Lehre der Geschichte der Pharmazie, stellt Wissen über die Fachrichtung zur Verfügung und fördert die Anerkennung dieser Disziplin. - [Engl.:] The ISHP is established to form an international centre for handling all matters of a pharmaceutical historical nature without commercial interests. It promotes research in writing and teaching history of pharmacy as well as disseminating knowledge and obtaining recognition for the discipline